2013
DOI: 10.1002/acr.21867
|View full text |Cite
|
Sign up to set email alerts
|

Updated Analysis of Standardized Photoprovocation in Patients With Cutaneous Lupus Erythematosus

Abstract: Objective. To determine the frequency and reproducibility of standardized photoprovocation in patients with cutaneous lupus erythematosus (CLE) and report our long-term experience. Methods. Photoprovocation using a standardized protocol was evaluated retrospectively in 566 patients. A diagnosis of CLE was clinically and/or histologically confirmed in 431 patients, and 315 patients with polymorphic light eruption (PLE) were additionally included as controls. Data were statistically analyzed using an SPSS databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 37 publications
0
20
0
4
Order By: Relevance
“…Standardized photoprovocation testing in a multicenter trial demonstrated that lesions were inducible in half of CLE patients, however may not be reproducible, and the authors suggested that UVA and UVB exposure may be a clinically and academically useful means for evaluating photosensitivity and disease activity [48,49]. …”
Section: How Can We Properly Diagnose Cle?mentioning
confidence: 99%
“…Standardized photoprovocation testing in a multicenter trial demonstrated that lesions were inducible in half of CLE patients, however may not be reproducible, and the authors suggested that UVA and UVB exposure may be a clinically and academically useful means for evaluating photosensitivity and disease activity [48,49]. …”
Section: How Can We Properly Diagnose Cle?mentioning
confidence: 99%
“…UV provocation was performed based on a published protocol designed for use in clinical trials (91,92). Briefly, a solar simulator was used in routine clinical practice, which replicated the protocol of UV-A and UV-B provocation in a single exposure.…”
Section: Uv Provocationmentioning
confidence: 99%
“…In a multicenter study of 47 subjects with CLE, a standardized photoprovocation protocol caused UV-induced lesions in about half of all patients, with the highest rates observed in those with SCLE and LET [11]. An updated retrospective analysis revealed even higher rates of positive photoprovocation (61.7%) [12]. Photoprotection thus represents a key component of preventative therapy in CLE, and the consistent use of sunscreens is commonly recommended for these patients [13].…”
Section: Non-pharmaceutical Interventionsmentioning
confidence: 99%